Familial transient financial difficulties during infancy and long-term developmental concerns. Issue 12 (3rd April 2017) - Ramanathan, S.; Balasubramanian, N.; Faraone, S. V.
Abstract : Background: Socioeconomic difficulties affect the cognitive and emotional development of children. However, the focus of prior studies has largely been on poverty and material hardship. This study expands on the existing literature by examining the impact of familial transient financial difficulties during infancy on long-term cognitive and behavioral outcomes. Methods: The National Longitudinal Surveys of Youth (79) were used to assess the association between a transient drop in family income by 50% or more (called transient income decline or TID) during the first 3 years of life and later-life Peabody Individual Achievement Math and Reading scores and behavior problem index (BPI) scores ( N = 8272–17 348; median assessment age = 9 years). A subsample of matched siblings ( N = 2049–4238) was examined to tease out maternal and intra-familial effects. Results: Exposure to TID predicted increased total and externalizing BPI scores (std. coefficients of 0.10 and 0.09, respectively, p < 0.01) in the overall sample. Among matched siblings, exposure to TID predicted increased total, externalizing, and internalizing BPI scores (std. coefficients of 0.27, 0.25, and 0.23, respectively, p < 0.01). Conclusion: Familial transient financial difficulties can have long-lasting behavioral effects for infants. The study identifies an early risk factor and at-risk children, thus providing insight into developing early intervention measures for infants to avoid long-term behavioral problems.